Robust controllers design for a distillation column - Hurtado Cortés, Luini Leonardo; Forero Casallas, Jhon Alejandro; Villarreal López, Luís (Tecnura, 2017)
Objective: This paper presents the design of robust controllers for a distillation column using a graphical editor. The graphical tool simplifies the design process. Methods: The graphical editor helps calculate weighting functions of the performance criteria and the uncertainty of the plant due to disturbances, and perform their interconnection. Subsequently, three types of controllers were designed and analyzed the robustness. Results: We performed closed loop simulations on the non-linear model, modifying the values of the feed rate F and the feed composition zF, and assuming uncertainty in the parameters of the control valves and sensors. Conclusions: Closed loop simulations showed that the process achieves its stability by meeting the performance criteria. The obtained results for bottom compositions showed errors under 0.8%. The LMI controller obtained satisfactory results for top and bottom compositions under any kind of disturbance.